Quasiminimal distal function space and its semigroup compactification - R. D. Pandian (International Journal of Mathematics and Mathematical Sciences)
Quasiminimal distal function on a semitopological semigroup is introduced. The concept of right topological semigroup compactification is employed to study the algebra of quasiminimal distal functions. The universal mapping property of the quasiminimal distal compactification is obtained.